2021
DOI: 10.3390/photonics8100414
|View full text |Cite
|
Sign up to set email alerts
|

High Intensity Violet Light (405 nm) Inactivates Coronaviruses in Phosphate Buffered Saline (PBS) and on Surfaces

Abstract: It has been proven that visible light with a wavelength of about 405 nm exhibits an antimicrobial effect on bacteria and fungi if the irradiation doses are high enough. Hence, the question arises as to whether this violet light would also be suitable to inactivate SARS-CoV-2 coronaviruses. Therefore, a high-intensity light source was developed and applied to irradiate bovine coronaviruses (BCoV), which are employed as SARS-CoV-2 surrogates for safety reasons. Irradiation is performed in virus solutions diluted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 58 publications
5
11
2
Order By: Relevance
“…To our knowledge, this is the first report of 405 nm light-based inactivation of HIV-1 in human plasma. In line with the observations reported here, there have been reports of lipid-enveloped SARS-CoV-2 and Influenza A virus inactivation by 405 nm light whilst suspended in phosphate buffered saline (PBS) [13] and beta-coronaviruses (bovine) suspended in PBS as well as the virus suspension dried on steel surfaces [14]. Visible violet-blue light other than 405 nm wavelengths such as doses of 425 nm blue light were also reported to inhibit infection and replication of cell-associated SARS-CoV-2 by >99% 24 h post-infection and cell-free beta-coronaviruses including SARS-CoV-1, MERS-CoV, and SARS-CoV-2 up to 99.99% in a dose-dependent manner [15].…”
Section: Discussionsupporting
confidence: 90%
“…To our knowledge, this is the first report of 405 nm light-based inactivation of HIV-1 in human plasma. In line with the observations reported here, there have been reports of lipid-enveloped SARS-CoV-2 and Influenza A virus inactivation by 405 nm light whilst suspended in phosphate buffered saline (PBS) [13] and beta-coronaviruses (bovine) suspended in PBS as well as the virus suspension dried on steel surfaces [14]. Visible violet-blue light other than 405 nm wavelengths such as doses of 425 nm blue light were also reported to inhibit infection and replication of cell-associated SARS-CoV-2 by >99% 24 h post-infection and cell-free beta-coronaviruses including SARS-CoV-1, MERS-CoV, and SARS-CoV-2 up to 99.99% in a dose-dependent manner [15].…”
Section: Discussionsupporting
confidence: 90%
“…Competitive reactions of ozone with media components were assigned as one of the potential mechanisms that reduce the effectiveness of SARS-CoV-2 inactivation [38]. Bovine coronavirus has been shown to be sensitive to the high intensity violet light 405 nm after centrifugation in the culture medium and resuspension in a tenfold volume of phosphate buffered saline (PBS) [23]. This may just indicate the binding of endogenous PS from the culture medium to viral particles.…”
Section: Discussionmentioning
confidence: 99%
“…Decontamination of surfaces utilizes quaternary ammonium compounds [18] and other disinfectants, ozone exposure [19], and germicidal ultraviolet C (UVC, 100-280 nm) [20]. However, photodisinfection is not limited to antimicrobial effects of UVC 254 nm, and can be induced by almost all optical wavelengths [21], from far-UVC 222-nm [22] to high intensity violet light [23] and visible light activating production of reactive oxygen species (ROS) by photosensitizers (PS), namely photodynamic disinfection [24].…”
Section: Introductionmentioning
confidence: 99%
“…(30) recently demonstrated successful reductions in SARS‐COV‐2 upon exposure to low irradiance (0.035–0.6 mW cm −2 ) 405‐nm light, and additionally highlighted the increased susceptibility of lipid‐enveloped viruses in comparison with non‐enveloped viruses (identical irradiations achieved 2.3 log 10 reductions in SARS‐COV‐2 after 8 h and just 0.1 log 10 reductions in a non‐enveloped RNA virus after 24 h); suggesting the lipid envelope itself may instigate ROS production. Other studies have similarly demonstrated the susceptibility of SARS‐CoV‐2, or an appropriate surrogate, to 405‐nm light inactivation presented on surfaces and in liquid media, both in the presence and absence of photosensitizers (31–35). Although highly encouraging, these studies have primarily demonstrated inactivation using 405‐nm light at high irradiances (≥78.6 mW cm −2 ) or at low irradiances delivered at a very short distance (~2.3–25.4 cm) from the sample surface (30–35), however, it is of great importance to determine whether inactivation of SARS‐CoV‐2 can be achieved under conditions which more accurately represent those which would be safely and practically implemented for environmental decontamination of communal areas.…”
Section: Introductionmentioning
confidence: 92%
“…Other studies have similarly demonstrated the susceptibility of SARS‐CoV‐2, or an appropriate surrogate, to 405‐nm light inactivation presented on surfaces and in liquid media, both in the presence and absence of photosensitizers (31–35). Although highly encouraging, these studies have primarily demonstrated inactivation using 405‐nm light at high irradiances (≥78.6 mW cm −2 ) or at low irradiances delivered at a very short distance (~2.3–25.4 cm) from the sample surface (30–35), however, it is of great importance to determine whether inactivation of SARS‐CoV‐2 can be achieved under conditions which more accurately represent those which would be safely and practically implemented for environmental decontamination of communal areas.…”
Section: Introductionmentioning
confidence: 92%